Brief report: Bereaved parents informing research design: The place of a pilot study. Issue 1 (2nd January 2019) - Donovan, L. A.; Wakefield, C. E.; Russell, V.; Hetherington, Kate; Cohn, R. J.
ABSTRACT: Background: Risk minimization in research with bereaved parents is important. However, little is known about which research methods balance the sensitivity required for bereaved research participants and the need for generalizable results. Aim: To explore parental experiences of participating in mixed method bereavement research via a pilot study. Design: A convergent parallel mixed method design assessing bereaved parents' experience of research participation. Setting/participants: Eleven parents whose child was treated for cancer at The Royal Children's Hospital, Brisbane completed the questionnaire/interview being piloted (n = 8 mothers; n = 3 fathers; >6 months and <6 years bereaved). Of these, eight parents completed the pilot study evaluation questionnaire, providing feedback on their experience of participation. Results: Participants acknowledged the importance of bereaved parents being central to research design and the development of bereavement programs. Sixty-three per cent (n = 5/8) of parents described completion of the questionnaire as 'not at all/a little bit' of a burden. Seventy-five per cent (n = 6/8) of parents opting into the telephone interview described participation as 'not at all/a little bit' of a burden. When considering the latest timeframes for participation in bereavement research 63% (n = 5/8) of parents indicated 'no endpoint.' Findings from the pilot study enabled important adjustments to be made to a large-scale future study. Conclusions: As a research method, pilot studies may be utilized to minimize harm and maximize the potential benefits for vulnerable research participants. A mixed method approach allows researchers to generalize findings to a broader population while also drawing on the depth of the lived experience.